2020
DOI: 10.1007/s10877-020-00549-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of positioning on cerebral autoregulation during radical prostatectomy: a prospective observational study

Abstract: Purpose Surgery in the prolonged extreme Trendelenburg position may lead to elevated intracranial pressure and compromise cerebral hemodynamic regulation. We hypothesized that robot-assisted radical prostatectomy with head-down tilt causes impairment of cerebral autoregulation compared with open retropubic radical prostatectomy in the supine position. Methods Patients scheduled for elective radical prostatectomy were included at a tertiary care prostate cancer clinic. Continuous monitoring of the cerebral aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Pooled data from three prospective observational studies were analysed. The studies were primarily designed to (1) compare cerebrovascular autoregulation (CVA) between robot-assisted radical prostatectomy in the extreme Trendelenburg position and open retropubic surgery in supine position [ 15 ]; (2) describe patterns of functional connectivity measured with 64-channel electroencephalogram and their association with cognitive function in the perioperative period (unpublished data); (3) assess the association between intraoperative CVA and DNCR after major non-cardiac surgery (unpublished data) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pooled data from three prospective observational studies were analysed. The studies were primarily designed to (1) compare cerebrovascular autoregulation (CVA) between robot-assisted radical prostatectomy in the extreme Trendelenburg position and open retropubic surgery in supine position [ 15 ]; (2) describe patterns of functional connectivity measured with 64-channel electroencephalogram and their association with cognitive function in the perioperative period (unpublished data); (3) assess the association between intraoperative CVA and DNCR after major non-cardiac surgery (unpublished data) …”
Section: Resultsmentioning
confidence: 99%
“…Impaired CVA during head-down position for robot-assisted radical prostatectomy has been observed in a prospective study [ 31 ]. By contrast, our research group has previously shown that open radical prostatectomy in the supine position and robot-assisted surgery in the extreme Trendelenburg position with capnoperitoneum do not differ with regard to CVA impairment [ 15 ]. In contrast to radical prostatectomy, which is recommended as a curative treatment option for patients with localized cancer and a life expectancy of > 10 years, procedures for solid tumors other than prostate cancer are frequently performed at more advanced disease stages and may involve patients with higher perioperative risk [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beck et al [ 35 ] hypothesized that an impairment in cerebrovascular autoregulation due to elevated intracranial pressure could be found in patients undergoing robot-assisted radical prostatectomy in the extreme head-down (Trendelenburg) position. Cerebral autoregulation was continuously assessed by calculating the cerebral oxygenation index, but no differences in cerebral autoregulation were demonstrated between robot-assisted (head-down position) and open radical prostatectomy (supine position).…”
Section: Tissue Oxygenation Monitoring In Critical Illness and Non-ca...mentioning
confidence: 99%